2018
DOI: 10.1177/0361198118792334
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Games to Study Transportation Issues and Solutions: Studies on Synchromodality

Abstract: In this paper we discuss the application of simulation gaming to study the behavior and decision making of stakeholders when confronted with complex transportation problems. The problem we tackle is synchromodal transportation. Synchromodality requires the vertical and horizontal collaboration of stakeholders in all the levels of decision making. To facilitate this, we develop four games designed in a way that meets the needs of decision makers in each level. We present both board and digital games and the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Finally, our participatory modelling approach is based on a simulation game that represents a real STS at a certain level of abstraction, and participants who work together to complete the aim of the game (Kourounioti et al, 2018). The idea behind engaging with stakeholders this way is to promote:…”
Section: Final Decisionsmentioning
confidence: 99%
“…Finally, our participatory modelling approach is based on a simulation game that represents a real STS at a certain level of abstraction, and participants who work together to complete the aim of the game (Kourounioti et al, 2018). The idea behind engaging with stakeholders this way is to promote:…”
Section: Final Decisionsmentioning
confidence: 99%
“…In literature SGs have been already applied but mostly for passenger transport ( [25] [26], [27], [28], [29]), while the freight transport examples remain limited ( [30], [31], [32], [33], [34]. In previous work [32] discuss the use of games for the governance of the transport system in a whole, and to create awareness for sycnhromodal transport solutions in particular. In [35]students were given the role of economic agents that interacted with truckers to study the formation of the truck tour.…”
Section: Litterature Reviewmentioning
confidence: 99%
“…Freese, Lukosch, Wegener and König Serious games as research instruments -Do's and don'ts from a cross-case-analysis in transportation Games as research instruments in freight transportation. Serious games are an accepted tool in exploring freight transportation aspects as shown in the works of several authors (Kourounioti et al, 2018;Kurapati et al, 2015;Kurapati et al, 2017;Meijer, 2009). While Meijer (2009) addresses a problem on a strategic level, Kurapati et al (2015) suggest the use of short games on an operational level in transportation.…”
Section: Yard Crane Scheduler -A Serious Game For Freight Transportationmentioning
confidence: 99%
“…While Meijer (2009) addresses a problem on a strategic level, Kurapati et al (2015) suggest the use of short games on an operational level in transportation. Kurapati et al (2017) as well as Kourounioti et al (2018) discuss the use of games for the governance of the transport system as a whole, and awareness for synchromodal transport solutions in particular. The above studies have shown that serious games are valuable research instruments on different levels in freight transportation, as they represent controllable, safe environments that allow both for experimentation and for observation of behaviour and decision-making processes.…”
Section: Yard Crane Scheduler -A Serious Game For Freight Transportationmentioning
confidence: 99%